Cedera Paru pada Near Drowning : Patofisiologi dan Penatalaksanaan - Muhammad Mirsa Nidzarsyah; Suryani Padua Fatrullah (Faculty of Medicine, Universitas Mataram, 2026)
Near drowning is a major cause of respiratory emergencies and can lead to significant pulmonary complications. Aspiration of water disrupts normal lung function, resulting in hypoxemia, surfactant washout, alveolar collapse, and in severe cases, acute lung injury or ARDS. The extent of injury is influenced by several factors, including the amount of aspirated water, contamination with pathogens, and the victim’s physiological condition at the time of submersion. Both freshwater and seawater aspiration can produce similar clinical consequences, ultimately impairing gas exchange and triggering an inflammatory response in the lungs. Early assessment and management are crucial to prevent deterioration. Key evaluations include monitoring oxygen saturation, arterial blood gases, chest radiography, and continuous clinical observation to detect early signs of respiratory compromise. Management focuses on maintaining adequate oxygenation, preventing further heat loss, and addressing complications such as pulmonary edema or infection. The use of positive end-expiratory pressure (PEEP) may be required in patients who develop significant hypoxemia. Near drowning victims who remain asymptomatic after four to six hours of observation generally have a good prognosis, while those with aspiration require close monitoring due to the risk of delayed respiratory failure.